2013
DOI: 10.3390/en6052562
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the Operational Noise from Full Scale Wave Energy Converters in the Lysekil Project: Estimation of Potential Environmental Impacts

Abstract: Abstract:Wave energy conversion is a clean electric power production technology. During operation there are no emissions in the form of harmful gases. However there are unsolved issues considering environmental impacts such as: electromagnetism; the artificial reef effect and underwater noise. Anthropogenic noise is increasing in the oceans worldwide and wave power will contribute to this sound pollution in the oceans; but to what extent? The main purpose of this study was to examine the noise emitted by a ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 53 publications
1
12
0
8
Order By: Relevance
“…In accordance with such details, the changes in the patterns of wind have significant consequences for the development of wave energy [75]. This is further illustrated below:…”
Section: Potential Impacts Of Wave Energymentioning
confidence: 77%
“…In accordance with such details, the changes in the patterns of wind have significant consequences for the development of wave energy [75]. This is further illustrated below:…”
Section: Potential Impacts Of Wave Energymentioning
confidence: 77%
“…No studies regarding the operational noise of WECs have analysed the data in view of engineering features towards exploring AE as a condition monitoring technique. This application was briefly mentioned in a very small number of reports as a future development possibility [19,47] and has been recently trialled for a tidal energy deployment [48].…”
Section: Discussionmentioning
confidence: 99%
“…Verdant tidal turbines generated "more noise than was expected" [29], and it was later found that a blade on one of the six turbines was broken and another was subject to an incipient failure. Measurements of two point absorber WECs at Lysekil [33] reported a number of 1-s high-amplitude impulses that saturated the recorder (up to 20 kHz). These impulses were found to be due to impacts on the end stop within the WECs.…”
Section: Underwater Acoustic Monitoringmentioning
confidence: 99%